THE CONSEQUENCES OF OPERATING FRAUD ON THE MORPHOMETRIC GROWTH OF THE MAXILLOFACIAL REGION IN CHILDREN WITH PALATE SPLITS AND CONGENITAL LIP DURING THE FIRST AND SECOND CHILDHOOD PERIODS - Shakhnoza Alixuseynovna, Kambarova (Research Journal of Trauma and Disability Studies, 2023)
Congenital abnormalities of the teeth, jaws, and face are common and frequently serious conditions that pose a challenge to surgical dentistry and maxillofacial surgery. Globally, there has been a noticeable rise in the number of children born with congenital defects of the face and jaw. Specifically, congenital cracks of the palate and upper lip make up roughly 13% of all congenital abnormalities in humans.